FRI0307 LENABASUM, A CANNABINOID TYPE 2 RECEPTOR AGONIST, REDUCES CD4 CELL POPULATIONS AND DOWNREGULATES TYPE 1 AND 2 INTERFERON ACTIVITIES IN LESIONAL DERMATOMYOSITIS SKIN. (June 2019) - Chen, Kristen; Zeidi, Majid; Reddy, Nithin; White, Barbara; Werth, Victoria
Abstract : Background: Lenabasum is a synthetic, non-immunosuppressive, selective cannabinoid receptor type 2 (CB2) agonist that activates resolution of innate immune responses. CB2 is a G-protein coupled receptor found primarily on activated immune cells. In vitro, it has shown to affect T-cell activity, alter Th1 and Th2 cytokine production, and decrease type 1 interferon activity. Objectives: We sought to characterize the in vivo effect of lenabasum on inflammatory cells and cytokines thought to be involved in the itch and disease pathogenesis of dermatomyositis (DM). Methods: 22 adult patients with refractory, skin-predominant DM on stable standard-of-care treatments were recruited for a double-blind, placebo-controlled, randomized trial. Treatment was initially administered orally at a dose of 20 mg a day for 4 weeks, and subsequently raised to 20 mg twice a day for an additional 8 weeks. In a subset of subjects, lesional skin biopsies were collected at baseline and at Week 12. Tissues were stained via immunohistochemistry for IFN-beta, IFN-gamma, IL-4, IL-13, IL-33, IL-31, IL-31 RA, CB2 receptor, PPAR-gamma, CD4, CD8, CD69, CD11c, and mast cells. RT-PCR for IFN-beta, IFN-gamma, IL-31, IL-4, STAT6, and ST2 was performed on tissue RNA. Protein expression was quantified either by percent area positive or cells per HPF in the dermis. Statistical analyses were performed using the Wilcoxon signed-rank test. Results: CD4 expression in the skin biopsies from lenabasum-treated subjects significantly decreased at Week 12 compared to the placebo group (p<0.05). There were significant reductions in IFN-beta mRNA and protein, as well as IFN-gamma mRNA and protein at Week 12 in subjects on lenabasum compared to placebo (p < 0.05). IL-31 protein (p < 0.01) was reduced at Week 12 in subjects who received lenabasum, but IL-31RA protein did not change. CB2 protein decreased significantly in the lenabasum group compared to placebo. There were no changes in IL-4, IL-13, IL-33, and PPAR-gamma protein, or the number of CD8, CD69, CD11c, or mast cells in either group. There was no significant difference in IL-31, IL-4, STAT6, or ST2 mRNA expression. Conclusion: Lenabasum reduces Type 1 and 2 interferon levels as well as T-helper cell inflammation in subjects with DM. These effects have the potential to inhibit underlying disease pathways in DM, thus contributing to clinical improvement. References: [1] Kim, H.J., Zeidi, M., Bonciani, D., Pena, S.M., Tiao, J., Sahu, S. and Werth, V.P. Itch in dermatomyositis: the role of increased skin interleukin-31. British Journal of Dermatology. 2018;179(3):669-678. [2] Robinson ES, Alves P, Bashir MM, Zeidi M, Feng R, Werth VP. Cannabinoid Reduces Inflammatory Cytokines, Tumor Necrosis Factor-α, and Type I Interferons in DermatomyositisInVitro. J Invest Dermatol. 2017;137(11):2445 [3] Wong D, Kea B, Pesich R, Higgs BW, Zhu W, Brown P, et al. Interferon and biologic signatures in dermatomyositis skin: specificity and heterogeneity across diseases. PLoS One. 2012;7(1):e29161. Disclosure of Interests: Kristen Chen: None declared, Majid Zeidi: None declared, Nithin Reddy: None declared, Barbara White Shareholder of: Corbus Pharmaceuticals, Inc., Employee of: Corbus Pharmaceuticals, Inc., Victoria Werth: None declared